Dampak Cerita Kisah Nabi dan Rasul terhadap Pendidikan Karakter Generasi Muda di Era Digital: Dampak Cerita Kisah Nabi dan Rasul terhadap Pendidikan Karakter Generasi Muda di Era Digital - Farhat Mahmudi (Pascasarjana UIN Raden Mas Said Surakarta, 2024)
Character education has become a crucial issue amidst the moral challenges faced by modern society. Phenomena such as rising criminal acts, corruption, child abuse, and human rights violations reflect a character crisis in Indonesia. Noble values such as honesty, responsibility, and empathy are increasingly fading. Religion-based character education can serve as a solution to building a morally upright and integrity-driven young generation. The stories of Prophets and Messengers provide concrete examples of leadership, patience, and piety that are relevant for daily life application. This study aims to explore the effectiveness of using the stories of Prophets and Messengers as a teaching medium in shaping the character of young people in the digital era. By leveraging digital media as a storytelling platform, students are not only encouraged to understand religious values but also to strengthen their critical thinking and morality. This study emphasizes the importance of synergy between character education and technology to meet the learning needs of the 21st century.